2020
DOI: 10.3390/nu13010019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Obesity on the Metabolism and Bioavailability of Polyunsaturated Fatty Acids during Pregnancy and Breastfeeding

Abstract: Prenatal and postnatal development are closely related to healthy maternal conditions that allow for the provision of all nutritional requirements to the offspring. In this regard, an appropriate supply of fatty acids (FA), mainly n-3 and n-6 long-chain polyunsaturated fatty acids (LCPUFA), is crucial to ensure a normal development, because they are an integral part of cell membranes and participate in the synthesis of bioactive molecules that regulate multiple signaling pathways. On the other hand, maternal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 183 publications
(221 reference statements)
2
24
0
Order By: Relevance
“…On the other hand, maternal obesity during pregnancy and lactation can alter PUFA metabolism, leading to decreased PUFA levels and synthesis [ 28 , 29 ] and impaired capacity for materno-fetal long-chain PUFA transfer [ 30 ]. It has also been shown that placental transfer of FA transporters is impaired by obesity [ 48 ], leading to reduced PUFA supply to the fetus [ 30 ]. The endogenous synthesis of DHA from ALA can be affected by obesity itself and obesity-related metabolic diseases [ 49 ], reducing the activity of Δ-5 and Δ-6 desaturase enzymes [ 28 ], leading to impaired DHA synthesis and lower content of n-3 long-chain PUFA in erythrocytes and breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, maternal obesity during pregnancy and lactation can alter PUFA metabolism, leading to decreased PUFA levels and synthesis [ 28 , 29 ] and impaired capacity for materno-fetal long-chain PUFA transfer [ 30 ]. It has also been shown that placental transfer of FA transporters is impaired by obesity [ 48 ], leading to reduced PUFA supply to the fetus [ 30 ]. The endogenous synthesis of DHA from ALA can be affected by obesity itself and obesity-related metabolic diseases [ 49 ], reducing the activity of Δ-5 and Δ-6 desaturase enzymes [ 28 ], leading to impaired DHA synthesis and lower content of n-3 long-chain PUFA in erythrocytes and breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased AA levels are associated with a pro-inflammatory state and an oxidative stress with short-and long-term consequences. It has recently been revealed that high levels of n − 6 LCPUFAs in maternal circulation found during pregnancy and lactation confer a higher risk of obesity and its complications, neuropsychiatric disorders, asthma, and cancer to the offspring [44]. When LA and ALA dietary contributions are similar, the formation of DHA is privileged over that of AA.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that maternal obesity modifies fatty acid profile, resulting in low n-3 and elevated n-6 PUFA levels in maternal circulation during pregnancy ( 44 , 45 ). These modifications of the fatty acid profile are associated with a pro-inflammatory state and oxidative stress with short- and long-term consequences in the fetus and neonate.…”
Section: Discussionmentioning
confidence: 99%